Studi Pembuatan Bumbu Bubuk Palekko Instan Dengan Metode Foam Mat Drying - Harfika; Salfiana; Syarifuddin, Rifni Nikmat; Muhanniah (Jurnal Pendidikan Teknologi Pertanian, 2023)
This research was conducted to determine the effect of adding egg white as a foam drying agent (foam-mat dryig) on ​​the physical, chemical and organoleptic properties of the resulting instant palekko powdered seasoning. This research was carried out using a completely randomized design (CRD) with 3 treatments. The treatment applied was the addition of different egg white concentrations to the spice composition, namely A (10%), B (15%), and C (20%), each treatment was repeated 3 times. The test parameters in this study include; yield, soluble time, moisture content, ash content, flavour, color, taste and texture. The research data were analyzed for diversity to determine the effect of the treatment on the test parameters, and if there was a significant effect then it was continued with Duncan's multiple range test to find out the real difference between the treatments. The results of the study revealed that the concentration of egg white as a foam-mat drying agent affected the yield, moisture content, ash content, and the taste of the instant palekko powder seasoning produced. The best treatment was obtained in treatment A, namely the addition of the palekko seasoning formula with an egg white concentration of 10%, which reached a treatment value of 5.44, with an average yield test result of 25.88; water content 13.43%; ash content 20.26%; dissolving time 0.31 gram/second; as well as a color preference level score of 5.4; smell 5.57; taste 5.41; and texture 5.37